Binaural Spatialization: Comparing Head Related Transfer Function Models for Use in Virtual and Augmented Reality Applications - Angelucci, Simone; Franchi, Fabio; Graziosi, Fabio; Rinaldi, Claudia (Multimedia Technology and Enhanced Learning, 2022)
This work is focused on the binaural spatialization, presenting an analysis of the most common solutions to understand and classify their advantages and drawbacks and to find the one that results in a better virtual/augmented experience on the basis of subjective tests. This work is a preliminary step toward the implementation of an augmented reality system for cultural heritage enjoyment exploiting spatial audio through low-cost devices. Two different models are implemented in order to avoid the use of non individualized HRTFs and results show promising opportunities that must be further exploited.